Spatial Relationships of Levees and Wetland Systems within Floodplains of the Wabash Basin, USA1. (25th April 2018) - Morrison, Ryan R.; Bray, Erin; Nardi, Fernando; Annis, Antonio; Dong, Quan
Abstract: Given the unique biogeochemical, physical, and hydrologic services provided by floodplain wetlands, proper management of river systems should include an understanding of how floodplain modifications influence wetland ecosystems. The construction of levees can reduce river–floodplain connectivity, yet it is unclear how levees affect wetlands within floodplains, let alone the cumulative impacts within an entire watershed. This paper explores spatial relationships between levee and floodplain wetland systems in the Wabash Basin, United States. We used a hydrogeomorphic floodplain delineation technique to map floodplain extents and identify wetlands that may be hydrologically connected to river networks. We then spatially examined the relationship between levee presence, wetland area, and other river network attributes within discrete subbasins. Our results show that cumulative wetland area is relatively constant in subbasins that contain levees, regardless of maximum stream order within the subbasin. In subbasins that do not contain levees, cumulative wetland area increases with maximum stream order. However, we found that wetland distributions around levees can be complex, and further studies on the influence of levees on wetland habitat may need to consider finer resolution spatial scales.